Psychosocial Correlates of Frequent Indoor Tanning among Adolescent Boys - Blashill, Aaron J. (2012)
The aim of the current study was to assess psychosocial correlates (i.e., perceived weight, weight control strategies, substance use, and victimization) of frequent indoor tanning in adolescent boys—a group at high risk for developing skin cancer. Participants (N = 7,907) were drawn from a nationally-representative sample of adolescent boys attending high school in the United States. Binary logistic regression revealed that extreme weight control strategies, particularly steroid use (odds ratio = 3.67) and compensatory vomiting (odds ratio = 2.34), along with substance use and victimization, were significantly related to frequent indoor tanning. These results highlight the role of appearance-changing, and health-risk behaviors in the context of frequent indoor tanning. Skin cancer prevention interventions may benefit from adopting approaches that integrate the treatment of body dissatisfaction and subsequent maladaptive behaviors.